HIV testing, care, and treatment experiences among the steady male partners of female sex workers living with HIV in the Dominican Republic - Fleming, Paul J. (AIDS Care, 2016)
Male steady partners of female sex workers (FSW) living with HIV represent a key population for treatment as prevention and/or pre-exposure prophylaxis (PrEP) interventions. This study uses data collected from male steady partners who were referred by FSW living with HIV participating in a multi-level HIV prevention and care intervention in Santo Domingo, Dominican Republic. We conducted a socio-behavioral survey and HIV-testing with all men (n=64) and 16 in-depth interviews with a sub-sample to obtain more depth. Thirty-five of the 64 participants were living with HIV; 27 were previously diagnosed and 8 were diagnosed during our study. As a result, 45% of men were members of a sero-discordant sexual partnerships. Of men with no previous HIV diagnosis (n=37), 15 had never been tested for HIV and 9 had not been tested in the past two years. Ninety-three percent of men previously diagnosed with HIV reported receiving HIV care in the past 6 months and 78% were taking anti-retrovirals. Low HIV testing was partly due to men not feeling at-risk for HIV, despite having an HIV-infected partner. Additionally, a lack of tailored care inhibited engagement in ARV treatment for those infected. HIV testing was low, highlighting a need for test-and-treat strategies. Men not living with HIV would benefit from regular testing and would be good candidates for pre-exposure prophylaxis. While almost all men who had been diagnosed with HIV were engaged in care and adherent to ART, future research should assess whether they are achieving optimal HIV outcomes for their health and prevention of ongoing transmission.